Malnutrition Survey among Children Aged One to Five Years in an Out-Patient Settiing - Oluwafemi RO; Alonge OA; Abiodun MT (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Background: Malnutrition, though rarely listed as the direct cause, is estimated to contribute to more than half of all childhood deaths in the developing countries. The vicious cycle of poverty, recurrent infections and ignorance remain the major predisposing factors to this disease. Objective: To determine the prevalence of malnutrition among children aged one to five years attending the Out-Patient Department (OPD) of a Nigerian Specialist Hospital, to describe the major associated co-morbidities and associated socio-cultural factors. Methods: All the children aged 1 to 5 years attending the OPD of Mother and Child Hospital, Akure, Nigeria were recruited into the study from September 2018 to November 2018. In addition to basic bio-data, sociodemographic data, and clinical diagnoses, the Z-scores of the anthropometric parameters were calculated using the WHO AnthroPlus software. Results: A total of 577 children were studied with a male preponderance of 58.1%. The prevalence of underweight, stunting and wasting were 18.5%, 15.9% and 20.8% respectively. Malaria was the leading co-morbidity both in its complicated and uncomplicated forms. The identified associated socio-cultural factors included low socioeconomic status, large family size and some paternal social habits. Conclusion: The prevalence rate of malnutrition among the children was high despite the high literacy and socioeconomic status of the parents.